(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
In a joint analysis of feminist and LGBTQ+ theories, the history and development of Brazilian society and law, the role of social movements and their impact on institutions, and the functions and provisions of Labor Law, this research aims to address the dimensions of paternity leave and the need for parity with maternity leave. It adopts the perspective of concepts such as care work, the sexual division of labor, LGBTQ+ rights, contemporary family structures in Brazilian society, duties of protection toward children and families, and labor rights as both transformative and preservative expressions of social structures. Through bibliographic research and analysis of past and current legislation, and considering the dimensions, impacts, and scope of paternity leave in Brazilian society, it is undeniable that its regulation is urgent and must establish equivalence with maternity leave in terms of duration, financial benefits, conditions, and social security nature, taking into account the new family forms and organizations recognized by law and Brazilian society.